Hal Koch, de politiske partier og Ungdomskommissionen - Møller, Jes Fabricius (Historisk Tidsskrift, 2017)
Hal Koch, the Political Parties and the Youth Commission Hal Koch (1904-1963) was Professor of Church History at the University of Copenhagen. During the German occupation of 1940-1945, he became Chairman of Dansk Ungdomssamvirke, a politically neutral umbrella organization, and gained a position as a prominent intellectual. From 1943, his social democratic sympathies became more explicit and in 1945, he was appointed head of a government commission with the task of examining the economic, social and cultural conditions of the Danish youth (the so-called Youth Commission). The commission sat for seven years and produced a total of 14 reports, in which it identified a series of problems and suggested solutions. Members of the commission were mainly representatives from all political parties. Hal Koch has been identified as an instrument of social democratic interests. There is no doubt that his sympathies, especially when it came to social issues, lay with social democracy. However, this first study based on the archives of the Youth Commission, shows that for the most part, the work of the commission was based on a broader consensus than might be suggested by a study of the public reception of the reports.